Pregunta
If \( C=x^{2}+8 x+3 \) and \( B=x-8 \), find an expression that equals \( 3 C+B \) in standard form. Answer Attempt 1 out of 2
Ask by Chavez Delgado. in the United States
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\( 3C + B = 3x^{2} + 25x + 1 \)
Solución
To find an expression that equals \( 3C + B \) in standard form, follow these steps:
1. **Given Expressions:**
\[
C = x^{2} + 8x + 3
\]
\[
B = x - 8
\]
2. **Multiply \( C \) by 3:**
\[
3C = 3(x^{2} + 8x + 3) = 3x^{2} + 24x + 9
\]
3. **Add \( B \) to \( 3C \):**
\[
3C + B = 3x^{2} + 24x + 9 + (x - 8)
\]
4. **Combine like terms:**
\[
3x^{2} + 24x + x + 9 - 8 = 3x^{2} + 25x + 1
\]
5. **Final Expression in Standard Form:**
\[
3C + B = 3x^{2} + 25x + 1
\]
**Answer:** \( 3C + B = 3x^{2} + 25x + 1 \)
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Extra Insights
First, let's calculate \( 3C \). Since \( C = x^2 + 8x + 3 \), multiplying this by 3 gives us: \[ 3C = 3(x^2 + 8x + 3) = 3x^2 + 24x + 9. \] Next, we add \( B = x - 8 \) to \( 3C \): \[ 3C + B = (3x^2 + 24x + 9) + (x - 8). \] Combining like terms: \[ 3C + B = 3x^2 + (24x + x) + (9 - 8) = 3x^2 + 25x + 1. \] Therefore, the expression that equals \( 3C + B \) in standard form is: \[ \boxed{3x^2 + 25x + 1}. \]
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium